Effect of Stress and Work Conflict on Employee Performance at PT. Indomarco Adi Prima Bengkulu Branch South Part - Muhammad Syukur Al Hidayat; Ida Ayu Made E M Gayatri; Iswidana Utama Putra (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to determine the effect of work stress and work conflict against employees at PT Indomarco Adi Prima Bengkulu Branch of the southern part of Bengkulu. Data output using a questionnaire using the instrument test analysis method, multiple linear regression, determination test, hypothesis test. The results showed the independent test of the employee performance regression model, which can be obtained information that the significance value of work stress (X1) of 0,000. This value is significantly less than a significance value of less than 0.05 so that it can be concluded that work stress (X1) significantly affects the performance of Karyjara (Y). The significance value of the work conflict (X2) is 0.000. This value is significantly less than a significance value of less than 0.05 so that it can be concluded that the Work Conflict (X2) significantly affects the performance of the Karya (Y). Southern Bengkulu Branch. This is shown by the results of the ANOVA test or T test shows the simultaneous test results of the employee performance regression model, which can be obtained that the significance value of the F test is 0,000. The value in the equation above refers to the table